Development of a Road Construction Material Selection System - Teck, Teh Kian (2006)
Millions of ringgits have been spent annually for road maintenance. The causes of road problems may be due to incorrect selection of pavement material. The study shows that there is the tendency for using the same pavement material for the whole stretch of a project. Some important factors that affect pavement material were not considered by road designers, because there is no systematic pavement material selection system available. At present, road designers refer to some road design standard procedures which are not updated consistently and there is little exposure to some other pavement materials. A systematic pavement material selection based on expert guidance to guide the road designers is needed. This thesis looks into the first development of a Road Construction Material Selection System (RC-MSS), based on the outcomes of questionnaires from the selected pavement experts using the Friedman’ statistical analysis and documented sources. The study also looks into what the practitioners want if a pavement material selection system is developed. The survey shows that pavement materials were governed by soil conditions, expected load repetitions and geometric features of vertical gradient and horizontal curvature. Besides, the selection of the appropriate construction materials for the various layers for various traffic-loading under the type of terrains such as flat, rolling and mountainous was incorporated as important parameters. All these factors were found to be indispensable in the formulation of a material selection system for road construction. In the Friedman hypothesis testing of this study, it was found that there is significant difference in terms of durability, performance and ease of construction from each suggested pavement material in nine site conditions out of 30 site conditions. Multiple comparisons have been used to the rejected null hypothesis to determine which materials were significantly different in these nine rejected null hypothesis site conditions respectively. Positions were then given to the pavement materials based on the outcomes from the multiple comparisons method. The factors were then incorporated into developing of the specific rules of the system framework and the 30 site conditions were associated with the documented source and used as knowledge database for the system. In order to make the system user-friendly, compatible and flexible, the system was developed into the software using a programming language. RC-MSS developed interfaces are easy to use and have non-complicated procedures. The user can go straight to the output fast. The system can help the user in better decision-making of pavement material selection as it provides more feasible alternative materials.